The Effectiveness Of The Combination Of Effleurage Massage And Warm Compresses In Reducing Back Pain In The Third Trimester Pregnant Women - Daniati, Octaviana; Sulistyorini, Chandra; Puspitasari, Dwi Ida; Meihartati, Tuti (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Back pain in pregnant women is one of the discomforts felt by pregnant women, especially in the third trimester of pregnancy. Back pain is a condition where pain is felt in the lumbosacral, which is caused by several factors, including enlargement of the uterus, changes in body pos, tension, and increased hormones. This back pain is a physiological thing felt by pregnant women, but it will turn pathological if not treated properly and will have a fatal impact on both the mother and the fetus in the womb. Back pain in pregnant women can be treated non-pharmacologically by applying a combination of effleurage massage and warm compresses.Purpose: This study aimed to determine the effectiveness of a combination of effleurage massage and warm compresses in reducing back pain in third-trimester pregnant women at UPT Tideng Pale Health Center.Method: This study used a quasi-experiment design with a pre-test and post-test approach with a control group. The number of participants in this study was 34, and they met the inclusion criteria, consisting of 17 respondents in the intervention group and 17 in the control group. The pain assessment instrument used the Numeric Rating Scale (NRS). Results: Based on the Wilcoxon test, the P-value was 0.000 < α (0.05), so Ha was accepted.Conclusion: This indicates a difference in the results of the post-test in the intervention group and the control group because there is a very significant difference; it shows that the combination of effleurage massage and warm compress is effective in reducing back pain for pregnant women in the third trimester at UPT Tideng Pale Health Center Tana Tidung Regency.Suggestion It is expected that pregnant women in the third trimester continue to apply a combination of effleurage massage and warm compresses to reduce back pain during pregnancy. Midwives and research sites should provide information to pregnant women about the use of this method as an alternative solution for back pain. Educational institutions are expected to use the results of this research as a reference in the development of midwifery science to improve the quality of midwifery care. In addition, researchers can further make the results of this study as a reference for further research Keywords: Effleurage Massage, Warm Compress, Back Pain ABSTRAK : EFEKTIVITAS KOMBINASI PIJAT EFFLEURAGE DAN KOMPRES HANGAT DALAM MENURUNKAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III Latar Belakang : Nyeri punggung pada ibu hamil merupakan salah satu ketidaknyamanan yang dirasakan oleh ibu hamil secara khusus pada ibu hamil Trimester ke III. Nyeri punggung merupakan kondisi dimana nyeri yang dirasakan pada daerah lumbosakral yang disebabkan oleh beberapa faktor diantaranya pembesaran rahim, berubahnya postur tubuh dan juga peningkatan hormon. Nyeri punggung ini merupakan hal fisiologis yang dirasakan oleh ibu hamil namun akan berubah menjadi patologis jika tidak ditangani dengan tepat akan berdampak fatal baik bagi ibu maupun janin dalam kandungan. Nyeri punggung pada ibu hamil dapat ditangani secara non farmakologis yaitu dengan menerapkan kombinasi effleurage massage dan kompres hangat.Tujuan : Untuk mengetahui efektivitas kombinasi effleurage massage dan kompres hangat terhadap pengurangan nyeri punggung pada ibu hamil trimester III di UPT Puskesmas Tideng Pale.Metode : Penelitian ini menggunakan desain quasy-eksperiment dengan pendekatan pre-test and post-test with control group. Jumlah sampel dalam penelitian ini adalah 34 orang yang memenuhi kriteria inklusi yang terdiri dari 17 responden pada kelompok intervensi dan 17 orang pada kelompok kontrol. Instrumen penilaian nyeri menggunakan Numeric Raiting Scale (NRS) Hasil: Berasarkan uji Wilcoxon menujukan nilai-Pvalue sebesar 0.000 < dari α (0.05), sehingga Ha diterima. Kesimpulan: Ada perbedaan hasil post test pada kelompok intervensi dan kelompok kontrol, karena ada perbedaan yang sangat signifikan.Kesimpulan : Kombinasi effleurage massage dan kompres hangat efektif terhadap pengurangan nyeri punggung ibu hamil trimester III di UPT Puskesmas Tideng Pale Kabupaten Tana Tidung.Saran Diharapkan bagi ibu hamil trimester III untuk tetap menerapkan kombinasi pijat effleurage dan kompres hangat untuk mengurangi nyeri pinggang saat hamil. Bidan dan tempat penelitian hendaknya memberikan informasi kepada ibu hamil tentang penggunaan metode ini sebagai alternatif solusi nyeri punggung. Instansi pendidikan diharapkan dapat menjadikan hasil penelitian ini sebagai acuan dalam pengembangan ilmu kebidanan untuk meningkatkan mutu pelayanan kebidanan. Selain itu, peneliti selanjutnya dapat menjadikan hasil penelitian ini sebagai referensi untuk penelitian selanjutnya Kata kunci : effleurage massage, kompres hangat, nyeri punggung